Modelling the local environmental impact of underground coal gasification - Roullier, Benjamin David (2017)
Underground coal gasification (UCG) has the potential to access vast resources of stored fossil energy in a safe, clean and environmentally sound manner. Previous experiments have however led to concerns around surface subsidence, groundwater pollution and water table lowering. These issues can be prevented through the use of appropriate site selection and an understanding of the processes which cause these effects. Numerical simulations provide a cost effective means of predicting these issues without the need for costly and publically opposed field trials.